Reliabilitas Kaliper Tinggi Lutut dalam Penentuan Tinggi Badan - Triya Ulva Kusuma; Ali Rosidi (Universitas 'Aisyiyah Yogyakarta, 2018)
This study was conducted with the aim to test the reliability of knee height calliper which is then used to determine body height. The design of this research was observational with cross sectional approach with 22 subjects from Nutritional Science Master of Diponegoro University 2017 students. The measurement of height was done by microtoise, while knee height measurement was done by knee height calliper which then converted with chumlea formula. The reliability of knee height calliper and microtoise are tested by the test-retest method and the Pearson-Product Moment correlation technique. The reliability test results of knee height calliper and microtoise showed each r value is 0.991 and 0.099. These results showed that knee height calliper and microtoise are equally reliable used to determine body height.